The impact of tobacco smoking on health and cessation among a cohort of smokers in Ibadan (2014)
This study was designed to assess the impact of tobacco smoking on health and cessation among a cohort of smokers in Ibadan, Nigeria. The study adopted the descriptive survey design and the purposive sampling method was used to select seventy respondents from three Local Government Areas in Ibadan. Self validated questionnaire was used to collect data for the study. The results got revealed the most prominent health problems among the tobacco smoking motorcyclists. Therefore, there is need for mental health professionals to develop appropriate psychotherapeutic interventions to facilitate cessation among tobacco smokers.